Semiotics of Medical Discourse - Yulia N. Ebzeeva; Natalia M. Dugalich (RUDN Journal of Language Studies, Semiotics and Semantics)
Medical discourse as an institutional discourse is considered simultaneously in several aspects: genre palette; discourse participants and their communicative strategies and speech behaviour; forms of communication between patient and doctor; methods and material for transmitting medical information; linguistic means of monocode, polycode and multimodal text of medical discourse; visual means of polycode and multimodal tests; functions implemented by texts of different types. The very identification of the boundaries of medical discourse will remain relevant. The objects of analysis are Russian-language memes, demotivators, which we understand as a type of Internet memes, caricatures on a medical topic, printed advertisements for medical drugs, services and events, and medical posters. The subject of the study are iconic signs, index signs and symbols of medicine. The novelty of the proposed study is the appeal to these elements of a polycode text as a system of signs that are subject to decoding to recognize the author’s intention; their use is not obligatory, while their quality of generalization allows expressing a larger volume of meanings, and the recipient of the text relies on them to identify the text as belonging to medical discourse. The research material are polycode (with verbal and iconic series) texts with a total volume of 500 examples obtained by continuous sampling from the Internet. The study showed that the semiotic system should be recognized as an important element of polycode texts of medical discourse, since each of the three types of signs is noted in the five genres under consideration and performs summarizing, attractive, organizing, replacing and comic functions in the text. As an object of decoding in polycode texts on medical topics, we examined individual examples of the use of precedent phenomena. The algorithm for analyzing the semiotic system of medical discourse can be used to analyze the semiotic system of other types of institutional discourse.